(untitled) (Philological Studies, 2019)
The development of collocational competence as a component of lexical competence with non-native speakers is one of the most fundamental, but also most challenging aims of second language acquisition, since collocations contribute to more natural communication in L2 (Borić, 2004). The development of collocational competence in Croatian as a Second Language (CSL) is an uninvestigated area (Burić i Lasić, 2012; Petrović, 2007) and so far the most detailed description of noun collocations in Croatian as first language was given by Blagus Bartolec (2014). The main goal of this research was to examine the receptive and productive knowledge of noun collocations regarding their frequency, collocational strength, and considering the CSL proficiency level. The research deals only with basic collocations having nouns as bases and adjectives as their collocators. The sample comprised of 70 students of Language exercises in Croatian as L2 at intermediate level (B1-B2). Before creating the research instruments (blank-filling tests), it was necessary to examine the associative strength of collocational elements by native speakers of Croatian. The analysis of the productive level tasks shows that subjects of lower CSL proficiency have very poor collocational competence, while subjects of higher CSL proficiency show an equal knowledge of noun collocations in the nominative case and in oblique cases.